Dummy-surface molecularly imprinted polymers on magnetic graphene oxide for rapid and selective quantification of acrylamide in heat-processed (including fried) foods. (15th April 2017) - Ning, Fangjian; Qiu, Tingting; Wang, Qi; Peng, Hailong; Li, Yanbin; Wu, Xiaqing; Zhang, Zhong; Chen, Linxin; Xiong, Hua
Highlights: Dummy surface molecular imprinting technology was firstly used in detection of acrylamide. Surface imprinting, magnetic separation, and graphene oxide were combined effectively. The DSMIPs-GO-Fe3 O4 showed high adsorption ability and rapid magnetic separation. The DSMIPs-GO-Fe3 O4 proved rapid separation and selective quantification of acrylamide in real samples. Abstract: Novel nano-sized dummy-surface molecularly imprinted polymers (DSMIPs) on a magnetic graphene oxide (GO–Fe3 O4 ) surface were developed as substrates, using propionamide as a dummy template molecule for the selective recognition and rapid pre-concentration and removal of acrylamide (AM) from food samples. These products showed rapid kinetics, high binding capacity (adsorption at 3.68 mg·g −1 ), and selectivity (imprinting factor α 2.83); the adsorption processes followed the Langmuir–Freundlich isotherm and pseudo-second-order kinetic models. Excellent recognition selectivity toward acrylamide was achieved compared to structural analogs, such as propionic and acrylic acids (selectivity factor β 2.33, and 2.20, respectively). Moreover, DSMIPs–GO–Fe3 O4 was used to quantify acrylamide in food samples, yielding satisfactory recovery (86.7–94.3%) and low relative standard deviation (<4.85%). Thus, our DSMIPs–GO–Fe3 O4 -based procedure was demonstrated to be a convenient and practical method for the separation, enrichment, and removal of acrylamide from food samples.